Os desafios da educação no processo de inclusão de crianças surdas - Almeida, Andreya Andrade de (Brasil, 2023)
Brazilian education is still a universe under construction and deaf children are not manage to fully develop their language, the Brazilian Sign Language - LIBRAS is the first language of the deaf child, but where is she currently literate?. The school must consider that the child's development and his superior mental functions are directly linked to social interaction. But how does the process of inclusion of deaf people in practice in schools. In order to understand the educational process, with focus on the specificities and challenges of deaf and hearing children, this study aims to understand the educational process, focusing on the specificities and challenges of children deaf and hearing people, through qualitative research a bibliographical, documental and of observation regarding the current laws that regulate education brasiliera with a focus on schools that serve this diversity. The results found were that, unfortunately, Brazilian education is lagging behind, there is no conducive educational environment for the inclusion of deaf and hearing children that provide quality interaction, which leads to the exclusion of deaf children from the system educational. It is emphatic to say that bilingual education/bilingual school needs urgently be applied, since education is a duty of the State and the right of every citizen since the 1988 Constitution of the Federative Republic of Brazil and complemented by the law of guidelines and bases published in 1996, thus contributing to the development of all individuals.